(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article focuses on the idea of interethnic harmony, the fact that all peoples of Uzbekistan are united and act on the basis of the national idea, the essence of this term and the principles (trends) of finding solutions in the social structure. For this reason, it is shown that at a time when various conflicts are currently raging among nations in the world, these innovations are being carried out in our country based on the advice of our experienced, wise, intelligent people.